Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper examines the sources of real growth in Guinea. It identifies and quantifies the impact on real GDP growth of both the exogenous shocks and the policy changes that have occurred since 2000. The paper offers, first, some empirical evidence on real GDP growth in Guinea and then analyzes the sources of growth using the standard framework of growth accounting. The paper also analyzes and quantifies the effect that some exogenous shocks and policy changes have had on growth.